Pengaruh Suplementasi Probiotik dalam Ransum Terhadap Kualitas Fisik Daging Itik - Wahyuni, Dyah; Arisuteja, Sofi; Sandi, Sofia; Yosi, Fitra (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
This research aim to find out the effect of probiotic in ration on physical quality (pH, water holding capacity, cooking loss and tenderness) of duck meat. The materials used was local duck supplemented probiotic into ration. Research’s method used was Completely Randomize Design (CRD) consisted of 7 treatments and 4 replications namely P1(basic ration/ control), P2 (basic ration+probiotic), P3 (basic ration+infected by E.coli), P4 (basic ration+infected by Salmonella), P5 (basic ration+probiotic+infected by E.coli), P6 (basic ration+ probiotic+infected by Salmonella) and P7 (basic ration+probiotic+infected by E.coli+Infected by Salmonella). The results showed that probiotic suplementation about 106 cfu/ml into ration were no significantly effect on physical quality (pH, water holding capacity, cooking loss and tenderness) of duck meat. Keywords: probiotic, ration, physical quality, meat, duck